A method for preparing CsPbX3 perovskite thin film on a large scale

The preparation of CsPbX3 perovskite films through drop coating and vacuum assisted methods has solved the problem of large-area perovskite solar cell films, achieved efficient and uniform film preparation and simple production process, and promoted the perovskite solar cell. commercial application.

CN114628549BActive Publication Date: 2024-12-27BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210337989.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2024-12-27
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

The prior art is difficult to prepare high-efficiency perovskite solar cell thin films on a large scale, which limits the commercial application of perovskite solar cells, especially the spin coating method has low production efficiency and high material waste, which is not suitable for large-scale production.

Method used

The CsPbX3 perovskite film was prepared by drop coating method and vacuum assisted method. By weighing CsX, PbX2 and DMAX dissolved in organic solvents, drip coating to form a wet film. After vacuum treatment, thermal annealing was performed to prepare uniform CsPbX3 perovskite. film.

Benefits of technology

The high uniformity and large-area preparation of CsPbX3 perovskite film are achieved, the production process is simplified, the material is fully utilized, suitable for large-scale production, and the potential of perovskite solar cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114628549B_ABST
    Figure CN114628549B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a CsPbX3 perovskite film on a large scale, comprising: first, adding different concentrations of CsX, PbX2 and DMAX to an organic solvent for dissolution to prepare a CsPbX3 perovskite precursor solution; second, dripping the precursor solution on a substrate to make it self-spread to obtain a wet film; vacuuming the obtained wet film to obtain a prefabricated film; and finally, thermally annealing the prefabricated film to obtain a flat, dense and highly uniform CsPbX3 perovskite film. The CsPbX3 perovskite film obtained by the method of the invention has certain potential in preparing perovskite solar cells on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optoelectronic materials and devices, and in particular relates to a method for preparing a CsPbX3 perovskite film on a large area. Background Art

[0002] In recent years, small-area devices (<1cm 2 ) has rapidly soared from 3.8% in 2009 to 25.7%; high efficiency, low cost and good stability make perovskite solar cells gradually commercialized, and one of the main factors limiting the commercialization of perovskite solar cells is the lack of a preparation process for large-scale preparation of perovskite solar cells. Spin coating is a simple method for preparing small-area films, but it is not suitable for large-scale production due to its low production efficiency and large material waste. By searching and consulting the prior art, it was found that the drop coating method can be used to prepare perovskite films on a large scale, and researchers have achieved the preparation of organic-inorganic hybrid perovskite films and battery devices by drop coating, thereby promoting the commercial application of perovskite solar cells.

[0003] As a light absorbing material, inorganic CsPbX3 (X is Cl, Br, I, or a mixture of multiple) perovskite is considered to be the most promising type of perovskite material because of its suitable band gap and high thermal stability. At present, although the efficiency of small-area devices prepared by spin coating has exceeded 20%, there are still huge challenges in the large-area preparation of perovskite films and batteries. Therefore, it is very important to develop a method for large-area preparation of CsPbX3 perovskite films and batteries. Summary of the invention

[0004] In order to solve the deficiencies of the above-mentioned prior art and to meet the needs of large-area preparation of perovskite solar cells, the present invention proposes a method for large-area preparation of CsPbX3 perovskite film, involving the use of drop coating and vacuum-assisted methods to prepare CsPbX3 perovskite film, thereby meeting the needs of large-area preparation of perovskite solar cells. The specific technical scheme of the present invention is as follows:

[0005] A method for preparing a CsPbX3 perovskite film on a large scale comprises the following steps:

[0006] S1: Weigh CsX, PbX2 and DMAX, add organic solvent to dissolve, and prepare CsPbX3 perovskite precursor solution;

[0007] S2: drop-coating the CsPbX3 perovskite precursor solution obtained in step S1 on the substrate to allow it to self-spread to obtain a wet film;

[0008] S3: vacuumizing the wet film obtained in step S2 to obtain a prefabricated film;

[0009] S4: The prefabricated film obtained in step S3 is subjected to thermal annealing to prepare a CsPbX3 perovskite film.

[0010] Furthermore, X in CsPbX3 and DMAX is one or more of Cl, Br, and I.

[0011] Furthermore, the organic solvent in step S1 is a mixture of one or more solvents selected from N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, γ-butyrolactone, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile.

[0012] Furthermore, in step S1, the molar ratio of CsX, PbX2 and DMAX is 1:1-2:0-2, and the concentration of the prepared CsPbX3 perovskite precursor solution is 0.0005-2 mol / L.

[0013] Furthermore, in step S2, the CsPbX3 perovskite precursor solution is drop-coated on the substrate, and the required solution is 1 to 1000 μL.

[0014] Furthermore, in step S2, the self-spreading time of the CsPbX3 perovskite precursor solution is 0 to 30 minutes.

[0015] Furthermore, in step S3, the prefabricated membrane needs to be stored under vacuum conditions for 0 to 180 minutes.

[0016] Furthermore, in step S3, 0<vacuum degree≤0.05MPa.

[0017] Furthermore, in step S4, the prefabricated film is thermally annealed at a temperature of 150 to 300° C. for a time of 1 to 30 minutes.

[0018] An application of the CsPbX3 perovskite film prepared by the aforementioned method in a perovskite solar cell.

[0019] The beneficial effects of the present invention are:

[0020] 1. CsX, PbX2, DMAX, DMAC, DMF, DMSO, etc. used in the present invention are all commonly used raw materials in industry and are easily available;

[0021] 2. The present invention uses DMAC as a solvent, and the CsPbX3 perovskite film prepared by vacuum-assisted drop coating has higher uniformity;

[0022] 3. The whole operation process of the present invention is simple, takes a short time, fully utilizes materials, and is easy to mass produce;

[0023] 4. The CsPbX3 perovskite film prepared by the drop coating method in the present invention has greater potential in the large-area preparation of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. By referring to the drawings, the features and advantages of the present invention will be more clearly understood. The drawings are schematic and should not be understood as limiting the present invention in any way. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:

[0025] Figure 1 This is a schematic diagram of the sample selection area of ​​the present invention;

[0026] Figure 2 The SEM images of the sample obtained in Example 1 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 1, (b) is the cross-sectional view of the edge area of ​​the sample in Example 1, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 1;

[0027] Figure 3 The SEM images of the samples obtained in Example 2 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 2, (b) is the cross-sectional view of the edge area of ​​the sample in Example 2, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 2;

[0028] Figure 4 The SEM images of the samples obtained in Example 3 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 3, (b) is the cross-sectional view of the edge area of ​​the sample in Example 3, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 3;

[0029] Figure 5 The SEM images of the samples obtained in Example 4 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 4, (b) is the cross-sectional view of the edge area of ​​the sample in Example 4, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 4;

[0030] Figure 6 The SEM images of the sample obtained in Example 5 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 5, (b) is the cross-sectional view of the edge area of ​​the sample in Example 5, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 5;

[0031] Figure 7The SEM images of the samples obtained in Example 6 of the present invention, wherein (a) is the surface morphology of the middle area of ​​the sample in Example 6, (b) is the cross-sectional view of the edge area of ​​the sample in Example 6, and (c) is the cross-sectional view of the middle area of ​​the sample in Example 6;

[0032] Figure 8 Schematic diagram of the method of the present invention. DETAILED DESCRIPTION

[0033] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0034] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0035] like Figure 8 As shown, a method for preparing a CsPbX3 perovskite film on a large area comprises the following steps:

[0036] S1: Weigh CsX, PbX2 and DMAX, add organic solvent to dissolve, and prepare CsPbX3 perovskite precursor solution;

[0037] Preferably, the organic solvent is a mixture of one or more solvents selected from N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N,N-dimethylacetamide (DMAC), γ-butyrolactone (GBL), N-methylpyrrolidone (NMP), 2-methoxyethanol (2ME), and acetonitrile (ACN).

[0038] Preferably, the molar ratio of CsX, PbX2 and DMAX is 1:1-2:0-2.

[0039] Preferably, the concentration of the prepared CsPbX3 perovskite precursor solution is 0.0005-2 mol / L.

[0040] In some embodiments, X in CsPbX3 and DMAX is one or more of Cl, Br, and I.

[0041] S2: drop-coating the CsPbX3 perovskite precursor solution obtained in step S1 on the substrate to allow it to self-spread to obtain a wet film;

[0042] Preferably, the CsPbX3 perovskite precursor solution is drop-coated on the substrate, and the required solution is 1 to 1000 μL.

[0043] Preferably, the self-spreading time of the CsPbX3 perovskite precursor solution is 0 to 30 minutes.

[0044] S3: vacuumizing the wet film obtained in step S2 to obtain a prefabricated film;

[0045] Preferably, the prefabricated membrane needs to be stored under vacuum conditions for 0 to 180 minutes.

[0046] Preferably, 0<vacuum degree≤0.05MPa.

[0047] S4: The prefabricated film obtained in step S3 is subjected to thermal annealing to prepare a CsPbX3 perovskite film.

[0048] Preferably, the prefabricated film is thermally annealed at a temperature of 150 to 300° C. for a time of 1 to 30 minutes.

[0049] An application of the CsPbX3 perovskite film prepared by the aforementioned method in a perovskite solar cell.

[0050] In order to facilitate understanding of the above technical solution of the present invention, the above technical solution of the present invention is described in detail below through specific embodiments. The edge area and the middle area of ​​the sample selected by SEM test of the present invention are as follows Figure 1 shown.

[0051] Example 1

[0052] This embodiment prepares a precursor solution based on DMAC solvent, and a method for preparing a perovskite film by vacuum-assisted coating of the perovskite precursor solution on FTO. The specific steps are as follows:

[0053] (1) CsI, PbI2 and DMAI (dimethylamine hydroiodide) were dissolved in 1 ml of DMAC at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0054] (2) Take 3 μL of the precursor solution obtained in step (1) and apply it on a 3×3 cm 2 The substrate was allowed to self-spread for 20 seconds to form a wet film, and then the film was stored at a vacuum degree of 0.02 MPa for 30 minutes to obtain a pre-film, and the pre-film was annealed at 200°C for 5 minutes to obtain a CsPbI3 perovskite film;

[0055] Figure 2 This is the SEM image of the sample obtained in Example 1. Figure 2 (a) It can be concluded that the surface of the sample obtained in Example 1 is flat, dense and uniform, and has a high film quality; Figure 2(b) and (c) are cross-sectional views of the edge region and the middle region of the sample of Example 1, respectively. Figure 2 (b) It can be concluded that the thickness of the edge region of the sample obtained in Example 1 is 450 nm. Figure 2 (c) It can be concluded that the thickness of the middle area of ​​the sample in Example 1 is 470 nm, and the thickness difference between the edge area and the middle area is only 20 nm. Therefore, it can be concluded that the CsPbI3 perovskite film prepared by vacuum-assisted drop coating using DMAC as the perovskite precursor solvent has good uniformity and good film quality.

[0056] Example 2

[0057] The method of this embodiment is the same as that of embodiment 1, except that the solvent used is DMF.

[0058] (1) CsI, PbI2 and DMAI were dissolved in 1 ml of DMF at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0059] (2) Take 3 μL of the precursor solution obtained in step (1) and apply it on a 3×3 cm 2 The substrate was allowed to self-spread for 20 seconds to form a wet film, and then the film was stored at a vacuum degree of 0.02 MPa for 30 minutes to obtain a pre-film, and the pre-film was annealed at 200°C for 5 minutes to obtain a CsPbI3 perovskite film;

[0060] Figure 3 The SEM images of the samples obtained in Example 2 are as follows: Figure 3 (a) It can be concluded that the sample obtained in Example 2 has a dense and uniform surface and has good film quality; Figure 3 (b) and (c) are cross-sectional views of the edge region and the middle region of the sample of Example 2, respectively. Figure 3 (b) It can be concluded that the thickness of the edge area of ​​the sample obtained in Example 2 is 1.5 μm. Figure 3 (c) It can be concluded that the thickness of the middle area of ​​the sample in Example 2 is 0.35 μm, and the thickness difference between the edge area and the middle area reaches 1.2 μm. It can be concluded that the thickness of the edge area and the middle area of ​​the CsPbI3 perovskite film prepared by vacuum-assisted drop coating using DMF as a solvent has a large difference, and the overall uniformity of the film is low.

[0061] Example 3

[0062] The method of this embodiment is the same as that of embodiment 1, except that the solvent used is DMSO.

[0063] (1) CsI, PbI2 and DMAI were dissolved in 1 ml of DMSO at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0064] (2) Take 3 μL of the precursor solution obtained in step (1) and apply it on a 3×3 cm 2 The substrate was allowed to self-spread for 20 seconds to form a wet film, and then the film was stored at a vacuum degree of 0.02 MPa for 30 minutes to obtain a pre-film, and the pre-film was annealed at 200°C for 5 minutes to obtain a CsPbI3 perovskite film;

[0065] Figure 4 The SEM images of the samples obtained in Example 3 are as follows: Figure 4 (a) It can be concluded that the sample obtained in Example 3 has a dense and uniform surface and has good film quality; Figure 4 (b) and (c) are cross-sectional views of the edge region and the middle region of the sample of Example 3, respectively. Figure 4 (b) It can be concluded that the thickness of the edge area of ​​the sample obtained in Example 3 is 0.4 μm. Figure 4 (c) It can be concluded that the thickness of the middle area of ​​the sample in Example 3 is 0.61 μm, and the thickness difference between the edge area and the middle area is 0.21 μm. It can be concluded that the difference in thickness between the edge area and the middle area of ​​the CsPbI3 perovskite film prepared by vacuum-assisted drop coating using DMSO as a solvent is lower than that of the perovskite film prepared using DMF as a solvent, but there is still a certain gap compared to the perovskite film prepared using DMAC as a solvent, and the overall uniformity of the film is relatively low.

[0066] Example 4

[0067] This embodiment prepares a precursor solution based on DMAC solvent, and a method for preparing a perovskite film by drop coating the perovskite precursor solution on FTO, heating at low temperature to evaporate the solvent, and annealing at high temperature. The specific steps are as follows:

[0068] (1) CsI, PbI2 and DMAI were dissolved in 1 ml of DMAC at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0069] (2) Take 3 μL of the precursor solution obtained in step (1) and apply it on a substrate with a size of 3×3 cm 2 The film was allowed to self-spread for 20 seconds to form a wet film, and the wet film was heated at 100°C for 20 seconds, and then annealed at 200°C for 5 minutes to obtain a CsPbI3 perovskite film;

[0070] Figure 5 The SEM images of the samples obtained in Example 4 are as follows: Figure 5 (a) It can be concluded that the sample obtained in Example 4 has poor coverage and has large holes; Figure 5 (b) and (c) are cross-sectional views of the edge area and the middle area of ​​the sample in Example 4, respectively. It can be clearly seen from the cross-sectional views that the coverage of the sample in Example 4 is poor, and there are many holes between the perovskite film and the substrate; and there is a significant difference in thickness between the edge area and the middle area of ​​the perovskite film, and the thickness uniformity of the perovskite film is poor.

[0071] Example 5

[0072] The method of this embodiment is the same as that of embodiment 4, except that the solvent used is DMF.

[0073] (1) CsI, PbI2 and DMAI were dissolved in 1 ml of DMF at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0074] (2) The wet film was heated at 100 °C for 20 s and then annealed at 200 °C for 5 min to obtain a CsPbI3 perovskite film;

[0075] Figure 6 The SEM images of the samples obtained in Example 5 are as follows: Figure 6 (a) It can be concluded that the sample obtained in Example 5 has obvious holes and a relatively rough surface; Figure 6 (b) and (c) are cross-sectional views of the edge area and the middle area of ​​the sample in Example 5, respectively. It can be clearly seen from the cross-sectional views that the coverage of the sample in Example 5 is poor, the grain distribution is uneven, and the overall morphology fluctuates greatly; and there is a significant difference in thickness between the edge area and the middle area of ​​the perovskite film, and the thickness uniformity of the perovskite film is poor.

[0076] Example 6

[0077] The method of this embodiment is the same as that of embodiment 4, except that the solvent used is DMSO.

[0078] (1) CsI, PbI2 and DMAI were dissolved in 1 ml of DMF at a molar ratio of 1:1:1 (specifically, 0.8 mmol CsI, 0.8 mmol PbI2 and 0.8 mmol DMAI) to obtain a precursor solution;

[0079] (2) The wet film was heated at 100 °C for 20 s and then annealed at 200 °C for 5 min to obtain a CsPbI3 perovskite film;

[0080] Figure 7 The SEM images of the samples obtained in Example 6 are as follows: Figure 7 (a) It can be concluded that the sample obtained in Example 6 has obvious holes, a rough surface, and a small grain size; Figure 7 (b) and (c) are cross-sectional views of the edge region and the middle region of the sample in Example 6, respectively. It can be clearly seen from the cross-sectional views that the coverage of the sample in Example 6 is significantly improved compared with that in Example 5. However, there is an obvious thickness difference between the edge region and the middle region of the perovskite film, and the overall uniformity of the perovskite film is poor.

[0081] In the present invention, the terms "first", "second", "third", "fourth" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. The term "plurality" refers to two or more, unless otherwise clearly defined.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing CsPbX3 perovskite thin films on a large scale, characterized in that: The following steps are involved: S1: Weigh CsX, PbX2 and DMAX, add organic solvent to dissolve, and prepare CsPbX3 perovskite precursor solution; S2: drop-coating the CsPbX3 perovskite precursor solution obtained in step S1 on the substrate to allow it to self-spread to obtain a wet film; S3: vacuumizing the wet film obtained in step S2 to obtain a prefabricated film; S4: performing thermal annealing on the prefabricated film obtained in step S3 to prepare a CsPbX3 perovskite film; The molar ratio of CsX, PbX2 and DMAX is 1:1~2:0~2, and the concentration of the prepared CsPbX3 perovskite precursor solution is 0.0005~2mol / L; The CsPbX3 perovskite precursor solution is drop-coated on the substrate, the required solution is 1 to 1000 μL, and the self-spreading time of the CsPbX3 perovskite precursor solution is 0 to 30 minutes.

2. The method according to claim 1, characterized in that X in CsPbX3 and DMAX is one or more of Cl, Br, and I.

3. The method according to claim 1 or 2, characterized in that: The organic solvent in step S1 is a mixture of one or more solvents selected from N,N-dimethylformamide, dimethyl sulfoxide, N,N-dimethylacetamide, γ-butyrolactone, N-methylpyrrolidone, 2-methoxyethanol, and acetonitrile.

4. The method according to claim 1, characterized in that: In step S3, the prefabricated membrane needs to be stored under vacuum conditions for 0 to 180 minutes.

5. The method according to claim 4, characterized in that In the step S3, 0<vacuum degree≤0.05MPa.

6. The method according to claim 1, characterized in that In the step S4, the prefabricated film is thermally annealed at a temperature of 150 to 300° C. for a time of 1 to 30 minutes.

7. Application of the CsPbX3 perovskite film prepared by the method as claimed in claim 1 in perovskite solar cells.